Learning Analytics in Education: Literature Review and Case Examples From Vocational Education. Issue 7 (9th November 2020) - Gedrimiene, Egle; Silvola, Anni; Pursiainen, Jouni; Rusanen, Jarmo; Muukkonen, Hanni
ABSTRACT: Vocational education and training (VET) remain overlooked in learning analytics (LA) research. This systematic literature review, using four databases and other sources, was carried out by analyzing selected 60 articles (2012–2017) to study the levels and stages of education that the reviewed LA literature examined. The review indicated that most of the analyzed papers focused on the course level, followed by student and institution levels in higher education. Few empirical studies have addressed LA use during the VET stage, particularly at the governmental level. We also considered ethical concerns and recommendations for further LA development in VET. It is suggested to use LA in knowledge transfer and integration between the classroom and workplace.